Identification and characterisation of ten microsatellite loci in the Noisy Scrub-bird Atrichornis clamosus using next-generation sequencing technology - Cowen, Saul; Allcock, R.; Comer, S.; Wetherall, John; Groth, D. (Springer, 2013)
The Noisy Scrub-bird is an endangered species of songbird endemic to the south coast of Western Australia that has undergone a major and prolonged population bottleneck. Using shotgun 454 next-generation DNA sequencing we have identified and characterised ten polymorphic microsatellite loci in this species. Observed allelic diversity was relatively low (2–5 alleles per locus) and significant deviations from Hardy–weinberg Equilibrium observed, although the presence of null alleles was onlypostulated for two loci. The microsatellite loci characterised in this study will be useful in a future population genetics studies in this endangered species.